A global synthesis of the effects of diversified farming systems on arthropod diversity within fields and across agricultural landscapes. (10th May 2017) - Lichtenberg, Elinor M.; Kennedy, Christina M.; Kremen, Claire; Batáry, Péter; Berendse, Frank; Bommarco, Riccardo; Bosque‐Pérez, Nilsa A.; Carvalheiro, Luísa G.; Snyder, William E.; Williams, Neal M.; Winfree, Rachael; Klatt, Björn K.; et al.
Abstract: Agricultural intensification is a leading cause of global biodiversity loss, which can reduce the provisioning of ecosystem services in managed ecosystems. Organic farming and plant diversification are farm management schemes that may mitigate potential ecological harm by increasing species richness and boosting related ecosystem services to agroecosystems. What remains unclear is the extent to which farm management schemes affect biodiversity components other than species richness, and whether impacts differ across spatial scales and landscape contexts. Using a global metadataset, we quantified the effects of organic farming and plant diversification on abundance, local diversity (communities within fields), and regional diversity (communities across fields) of arthropod pollinators, predators, herbivores, and detritivores. Both organic farming and higher in‐field plant diversity enhanced arthropod abundance, particularly for rare taxa. This resulted in increased richness but decreased evenness. While these responses were stronger at local relative to regional scales, richness and abundance increased at both scales, and richness on farms embedded in complex relative to simple landscapes. Overall, both organic farming and in‐field plant diversification exerted the strongest effects on pollinators and predators, suggesting these management schemes can facilitate ecosystem service providers without augmenting herbivore (pest) populations. Our results suggest that organic farming and plant diversification promote diverse arthropod metacommunities that may provide temporal and spatial stability of ecosystem service provisioning. Conserving diverse plant and arthropod communities in farming systems therefore requires sustainable practices that operate both within fields and across landscapes. Abstract : Organic farming and on‐farm plant diversification can reduce biodiversity loss and boost‐related ecosystem services like pollination and pest control. Using a global dataset, we found that both management schemes enhanced richness at local and regional scales, mainly by promoting rare taxa that are critical for ecosystem resilience. Positive effects were greatest for two groups of beneficial insects: pollinators and predators. We also found stronger impacts of farm management for fields embedded in complex landscapes.